Mutation screening of MSH2 and MLH1 mRNA in hereditary non-polyposis colon cancer syndrome. Issue 9 (September 1996) - Froggatt, N J; Brassett, C; Koch, D J; Evans, D G; Hodgson, S V; Ponder, B A; Maher, E R
Abstract : Germline mutations in four human mismatch repair genes (MSH2, MLH1, PMS1, and PMS2) have been reported to cause hereditary non-polyposis colon cancer syndrome (HNPCC). The identification of germline mutations in HNPCC kindreds allows precise diagnosis and accurate predictive testing. To investigate further the genetic epidemiology of HNPCC and the nature and frequency of germline mutations in this disorder, we studied 17 English HNPCC kindreds for germline mutations in MSH2 and MLH1. A previous genetic linkage study had suggested that most English HNPCC families will have mutations in one of these genes. Mutation analysis was performed in a three step process. (1) mRNA extracted from lymphoblastoid cell lines was analysed for gross rearrangements, (2) the in vitro transcription-translation (IVTT) assay was then performed to detect protein truncating mutations, and (3) partial cDNA sequencing of MSH2 or MLH1 was undertaken in families (n = 6) linked to MSH2 or MLH1 but without a detectable mutation. Seven different germline mutations were identified in eight of 17 (47%) kindreds (five in MSH2 and three in MLH1). In three cases there was a deletion of a single exon in MSH2 mRNA, three mutations resulted in a truncated protein product, and two missense mutations were identified by direct sequencing. Six mutations were novel. No precise correlation between genotype and phenotype was observed, although a MSH2 missense (Thr905Arg) mutation was associated with a susceptibility to multiple colorectal polyps. Age related risks for colorectal and uterine cancer were similar for MSH2 and MLH1 mutations.